Djabugay country : an Aboriginal history of tropical North Queensland - Bottoms, Timothy (Timothy David Reis) (St Leonards, N.S.W. : Allen & Unwin, 1999)
Culture and history of the Djabuganydji, Nyagali, Guluy, Buluwanydji and Yirrganydji peoples who speak dialects of Djabugay; Ancestors' stories; history of contact by sea and by land; setting up Mona Mona Mission near Flaggy Creek and operation of the Mission; Kyber Farm; Four Mile Beach Camp, Port Douglas; effects of the closure of Mona Mona Mission on 1/1/1963; life at Mantaka; handback of parcels of land at Mantaka and Kowrowa.
Includes index.
Bibliography: p. 127-132.
Keywords: Djabugay (Australian people) -- History; Aboriginal Australians -- Queensland -- Cairns Region -- History; Land rights - Handbacks; Stories and motifs; Social organisation; Stories and motifs - Cultural heroes; Djabugay / Tjapukai / Djabuganjdji language (Y106) (Qld SE55-01); Government policy - State and territory - Queensland; Djabugay / Tjapukai / Djabuganjdji people (Y106) (Qld SE55-01); Daily life; Religions - Christianity - Missions; Language - Vocabulary - Place names; Colonisation; History; Cairns Region (Qld.) -- Race relations -- History; Mona Mona (NE Qld SE55-02); Cairns (NE Qld SE55-02); Barron River (NE Qld SE55-02, SE55-05); Kowrowa (NE Qld SE55-02); Port Douglas (NE Qld SE55-01); Mareeba (NE Qld SE55-01, SE55-05); Kuranda (NE Qld SE55-02); Flaggy Creek (NE Qld SE55-02); Mantaka (NE Qld SE55-02)